Geometry of fraud - Galvis-Castañeda, Iván Eduardo (Editorial Pontificia Universidad Javeriana, 2017)
Understanding the phenomenon of fraud from the perspective of the fraudster has occupied the interest of various disciplines such as criminology, accounting, auditing, and psychology, among others. Although many of these disciplines start from the fraud triangle theory to explain it with the three fundamental variables –pressure, opportunity, and rationalization– in thisdocument we consider that it is necessary to incorporate three variables for the holistic understanding of the problem of fraud: knowledge, motivation, and innovation. At the same time, a reection is developed on the phenomenon of corporate fraud from a psychological perspective that includes perception, emotion, and action as constitutive elements of motivation and creativethinking in innovation.